2005
DOI: 10.1093/occmed/kqi007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B virus markers in municipal solid waste workers in Keratsini (Greece)

Abstract: Occupational exposure to waste is possibly associated with the acquisition of HBV infection. Immunization of MSWWs should be considered to reduce the risk of HBV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 14 publications
2
38
0
1
Order By: Relevance
“…These studies show the vulnerability of the workers who are exposed to infection without the appropriate immunization 5,21,22,26,29 .…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…These studies show the vulnerability of the workers who are exposed to infection without the appropriate immunization 5,21,22,26,29 .…”
Section: Discussionmentioning
confidence: 94%
“…Six of the studies concluded that workers collecting urban solid waste are exposed to greater risk when compared with those who have no exposure 19,21,22,23,24,25 , although one study found no such additional risk 5 . With regard to health care waste, three studies indicate higher risk among those collecting than those working with urban solid waste 26,27,28 , and a fourth study found none 29 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations